The global forest fund from Rio to IFF4: what issues remain - Joshi, M.; Chipeta, M.E. (Center for International Forestry Research, 2001)
The paper reviewed the ongoing international forest policy deliberation on finance issues, and specifically a proposal to establish an international forest fund. The paper includes annexes from the report of the final sessions of the Intergovernmental Panel on Forests and the Intergovernmental Forum on Forests. Justifications given for Global Forests Fund include the need to pay for international public goods produced by forests and for the cost of making the transition to sustainable forest management practices. Opponents of the Global Forest Fund advocate better use of the existing funds before calling for a new mechanism. This paper provide a basis for further discussion by the Oslo Workshop of issues left unresolved.